2022
DOI: 10.5858/arpa.2021-0299-oa
|View full text |Cite
|
Sign up to set email alerts
|

Concordance in Breast Cancer Grading by Artificial Intelligence on Whole Slide Images Compares With a Multi-Institutional Cohort of Breast Pathologists

Abstract: Context.— Breast carcinoma grade, as determined by the Nottingham Grading System (NGS), is an important criterion for determining prognosis. The NGS is based on 3 parameters: tubule formation (TF), nuclear pleomorphism (NP), and mitotic count (MC). The advent of digital pathology and artificial intelligence (AI) have increased interest in virtual microscopy using digital whole slide imaging (WSI) more broadly. Objective.— To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The addition of immunohistochemistry staining to determine separate populations of CD4+, CD8+, CD56+, and Treg lymphocytes will greatly improve our understanding of the tumor microenvironment and may add specificity to the prognostic capability of TILs, as these different populations of lymphocytes have differential effects on prognosis 4,17,19 . The use of artificial intelligence in pathologic grading to determine tumor prognosis has shown early promise in urologic malignancies 27 and breast carcinoma 28 . Work on breast cancer has also demonstrated that from a pathologic perspective, the incorporation of TILs as a clinical biomarker is a definite possibility 29 —the use of TILs in the prognostic stratification of HER2‐positive breast cancer is now strongly recommended for standard clinical practice 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of immunohistochemistry staining to determine separate populations of CD4+, CD8+, CD56+, and Treg lymphocytes will greatly improve our understanding of the tumor microenvironment and may add specificity to the prognostic capability of TILs, as these different populations of lymphocytes have differential effects on prognosis 4,17,19 . The use of artificial intelligence in pathologic grading to determine tumor prognosis has shown early promise in urologic malignancies 27 and breast carcinoma 28 . Work on breast cancer has also demonstrated that from a pathologic perspective, the incorporation of TILs as a clinical biomarker is a definite possibility 29 —the use of TILs in the prognostic stratification of HER2‐positive breast cancer is now strongly recommended for standard clinical practice 30 …”
Section: Discussionmentioning
confidence: 99%
“…4,17,19 The use of artificial intelligence in pathologic grading to determine tumor prognosis has shown early promise in urologic malignancies 27 and breast carcinoma. 28 Work on breast cancer has also demonstrated that from a pathologic perspective, the incorporation of TILs as a clinical biomarker is a definite possibility 29 -the use of TILs in the prognostic stratification of HER2-positive breast cancer is now strongly recommended for standard clinical practice. 30…”
Section: Discussionmentioning
confidence: 99%
“… 51 Very recently, Mantrala et al investigated the concordance rate in breast carcinoma grading as determined by the Nottingham Grading System between AI and pathologists using WSI. 27 However, the impact of assistance by AI in diagnosing various breast lesions on clinical utility has not been fully investigated. The present study revealed that medical students upregulated accuracy scores when using the assistance of the model and some students achieved the same or higher accuracy scores than pathologists, although the SSD model and medical students showed lower diagnostic accuracies than pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…The technology has been developed to digitize an entire glass slide (Whole slide imaging; WSI), 25 and various AIs to classify WSI have been reported. 19 , 26 , 27 , 28 WSI gives various advantages, such as the automated WSI scanner that automatically scans. 29 , 30 However, introducing WSI scanners and digital pathology system and managing huge amounts of digital data need a lot of money.…”
Section: Introductionmentioning
confidence: 99%
“…The grading and staging of breast cancer has a significant impact on prognosis [ 22 , 23 ]. The WHO takes the Nottingham grading system as the standard histological grading system for invasive breast cancer [ 24 , 25 ]. The evaluation indicators are the proportion of glandular duct formation, nuclear pleomorphism, and mitotic image count [ 26 ].…”
Section: Introductionmentioning
confidence: 99%